In Technology We Trust?: From a Subjective Self to an Extended Digital Self - Runehov, Anne L. C. (Philosophy, theology and the sciences, 2021)
While technological advancements have always changed the way we look at and interact with the world, no technology has changed our world and our experience of it more than computer technology. No other technology has progressed as fast or as far, and this evolution is continuing. Furthermore, not only has our experience of the world changed, but these new technologies have also changed us as never before and in a way beyond our comprehension and control. It is not possible to account for all consequences of these new technologies within the frame of the present article. Hence, my aim is to raise attention and to encourage further research. This article accounts for the apprehension of the self from different perspectives, i. e., from traditional philosophical understandings to contemporary perceptions of the self in a digital world. It reflects on four concerns of living in the digital era: concerns about health, privacy, fake news, and narcissism.